2013
DOI: 10.5539/ass.v10n2p64
|View full text |Cite
|
Sign up to set email alerts
|

Spending Behaviour of a Case of Asian University Students

Abstract: Recently, interest in exploring professional financial issues mainly money management was shown to be highly increased due to the societal awareness of its benefits. The skill of money management is a major tool in exercising control over them to obtain quality life as working adults. Stratified random sampling was used to examine the spending patterns of student population at one of Malaysia universities. Due to the habit of student expenditures on campus which was shown to influence the way money is managed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 0 publications
2
22
0
3
Order By: Relevance
“…The study also aims to rank ten most incurred spending categories by students from six faculties. Results indicated that five most incurred expenses were for hygiene products, study materials, telecommunications products and services, clothing and health products which aligned with Sorooshian and Teck (2014). Using CHAID, several average spending amounts were generated according to classifications that were based on eleven predictor variables.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study also aims to rank ten most incurred spending categories by students from six faculties. Results indicated that five most incurred expenses were for hygiene products, study materials, telecommunications products and services, clothing and health products which aligned with Sorooshian and Teck (2014). Using CHAID, several average spending amounts were generated according to classifications that were based on eleven predictor variables.…”
Section: Discussionmentioning
confidence: 99%
“…To determine type of expenditure, there were 16 expenditure types listed and respondents were asked to tick as many types of expenditures they incurred. The types of expenditures were gathered from various sources (Deloitte, 2019;Moody, 2018;OnCampus Research, 2018;Singh et al, 2018;Sorooshian & Teck, 2014) Data were analysed using SPSS version 22.0. To serve the first objective, which is to identify five most incurred spending categories by students, frequencies for each category were generated and ten categories with the most tick (√), were selected.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations